Complications Following Arthroscopic Rotator Cuff Repair and Reconstruction. Issue 1 (January 2018) - Desai, Vishal S.; Southam, Brendan R.; Grawe, Brian
Abstract : Arthroscopic rotator cuff repair is a commonly performed procedure with low morbidity; however, postoperative complications do occur and surgeons must be familiar with how to prevent and treat them. Despite the availability of revision strategies and treatment options, the prevention of complications and successful primary rotator cuff repair results in better functional outcomes. While some complications can be treated, resulting in a full recovery, others may result in permanent disability; patients should be counseled to have realistic expectations.